Health service and medication use of parents of childhood cancer survivors: a controlled comparison study. (3rd October 2021) - Hsu, Jing; Sansom-Daly, Ursula M.; Hetherington, Kate; Ellis, Sarah J.; Donoghoe, Mark W.; Cohn, Richard J.; Zentella-Tusie, Alejandra; Wakefield, Claire E.
Abstract: Background: Parents of childhood cancer survivors may be vulnerable to experiencing poor health outcomes, but little is known about how these parents use healthcare. This study investigated the nature and extent of survivors' parents' healthcare and medication use relative to a comparison group. We also examined whether demographic or cancer-related factors were related to healthcare use and whether healthcare use was associated with parents' general functioning. Methods: We conducted a cross-sectional study involving 55 parents of cancer survivors recruited through eight Australian hospitals, and 135 parents of children without a cancer diagnosis, through an online recruitment platform. Participants responded to a questionnaire assessing their health service usage, regular medications, general functioning (engagement activities including work/study) and anxiety and depression symptoms (using PROMIS short forms). We performed regression analysis to determine factors related to healthcare and medication use in parents of survivors. Results: More parents of survivors reported accessing mental health services than comparison parents (56% vs. 33%, p =.003), mainly due to their use of social workers. Fewer parents of survivors reported accessing other community health services, particularly general practitioners (51% vs. 78%, p <.001). Having a child survivor who was male was associated with greater use of community health services ( B = −0.67, p =.008). No other demographic or cancer-related variables were associated with health service use. Health service use was not associated with general functioning, but greater medication use was associated with higher anxiety scores ( B = 1.41, p =.008). Conclusion: Parents of childhood cancer survivors showed different patterns of health service use relative to comparison parents, but the extent of their use was not significantly linked with demographic or cancer-related variables. Comprehensive assessment of parents' needs in clinical encounters remains vital to identify and appropriately match support needs with available services.